Wyższe Studium Polskie przy Bibliotece Polskiej w Paryżu w 1945 roku - Chmielewski, Witold (Biuletyn Historii Wychowania, 2016)
Following the German occupation of the French capital city, an idea sprang up in the Polish intellectual circles to intensify propagation of Polish culture and knowledge of Poland among young Polish and French people. This concept was to be implemented in the Polish Library in Paris by a series of lectures organized by the Department of Science of the Polish YMCA1 in France in late 1944. The success of the lectures encouraged the Polish Library to launch the Polish College with the goal of making available to primarily Polish youth, studying and working in Paris, the achievements of Polish science and culture and to prepare the young people for work in Poland. The curriculum was developed and, as expected, the College’s operations were financed by the YMCA. Wacław Grzybowski, Ph.D., a former ambassador of Poland to the USSR, was appointed director of the College. The lecturers included illustrious intellectuals: priest Augustyn Jakubisiak, Ph.D., Franciszek Pułaski, Zygmunt Dygat, Irena Gałęzowska, Wieńczysław d’Ercville and many other. The College enjoyed considerable popularity among the students. The changing political situation in Poland put a stop to the promising operations of the College. To some extent, it was continued in the Catholic University of Paris ( the Institut Catholique de Paris). Since 1945, the University hosted the Centre for Slavic Studies where the Polish Section (Section Polonaise) was established. It is worth emphasising that an ambitious attempt at establishing studies for young Poles abroad was made in Madrid, on the initiative of the Polish ambassador, count Józef Potocki, representing in Spain the Polish government in London.